Impact of quadrivalent HPV vaccine dose spacing on immunologic response in women living with HIV. Issue 15 (30th March 2020) - McClymont, Elisabeth; Ogilvie, Gina; Albert, Arianne; Johnston, Angela; Raboud, Janet; Walmsley, Sharon; Lipsky, Nancy; Loutfy, Mona; Trottier, Sylvie; Smaill, Fiona; Yudin, Mark H.; Klein, Marina B.; et al.
Abstract: HPV vaccination schedules have changed as evidence has supported reduced dosing and extended intervals. Women living with HIV (WLWH) represent an important population with no data on alternative dosing. Girls and WLWH received quadrivalent HPV (qHPV) vaccine in a pan-Canadian study of immunogenicity and efficacy. Serology was performed at months 0/2/7/12/18/24. Medical and sexual history was collected throughout. Linear regression was used to determine if spacing of doses was associated with peak antibody titer. Multivariable analyses demonstrated significant relationships between peak antibody titer and time to blood draw post last vaccine dose, naivety to the relevant HPV type, and HIV viral load for all qHPV types. There was a significant relationship between peak HPV16/18 antibody titer and age. Taking age, time to serology, CD4 cell count, CD4 nadir, HIV viral load, and HPV naivety into account, spacing of the three qHPV vaccine doses did not significantly impact peak antibody titers.